Delayed Post-Traumatic Spinal Cord Infarction with Quadriplegia: A Case Report - Tae Hoon Kim (Journal of Trauma and Injury)
Traumatic spinal cord infarction is a rare condition that causes serious paralysis. The regulation of spinal cord blood flow in injured spinal cords remains unknown. Spinal cord infarction or ischemia has been reported after cardiovascular interventions, scoliosis correction, or profound hypotension. In this case, a 52-year-old man revisited the emergency center with motor and sensory abnormalities in all four extremities 56 hours after a motor vehicle collision. Despite the clinical presentation and imaging examination, there were no specific findings on the patient’s first visit to the trauma center. Cervical spine computed tomography angiography showed a narrow vertebral artery, and diffusion-weighted imaging revealed spinal cord infarction from C3 to C5 with high signal intensity. It should be kept in mind that delayed-onset spinal cord infarction may occur in minor or major trauma patients as a result of head and neck injuries.